DEFINITION OF THE CONCEPT OF LAW ENFORCEMENT: THEORETICAL AND LEGAL ASPECTS - Kliuchkovych, Vasyl Yuriiovych (SUPREMANCE OF LAW, 2019)
The article investigates modern scientific approaches to understanding the concept of judicial enforcement. The relationship of judicial enforcement with related phenomena is revealed. It is emphasised that judicial enforcement should be considered as the form of application of law; as a leading function of judicial authorities; as a means of achieving justice. Definition of the concept of judicial enforcement is formulated. The essence, content and form of judicial enforcement are defined.